Network crafting, goal attainment, and work-to-family facilitation among hotel employees: the mediating roles of positive affect and information exchange - Zhang, Hongshuo; Liu, Jiakun; Wang, Huatian; Li, Kongqi (Frontiers in Psychology, 2023)
Background The hospitality industry is experiencing new developmental opportunities after the coronavirus pandemic, such as the expansion of digital presence, the introduction of wellness offerings to cater to health-conscious guests, and a growing focus on local and sustainable tourism. However, despite these positive changes, we still lack knowledge on how hospitality workers can proactively adjust their work conditions to excel in their professional domain while also flourishing in their family domain. Thus, the current study proposed and examined how network crafting behaviors can have positive effects on hotel employees’ work goal attainment and work-to-family facilitation. Based on the affectivity theories and the social cognitive theory, we examined the mediating roles of positive affect and information exchange on the relationship between network crafting behaviors and work goal attainment and work-to-family facilitation. Methods We collected data from three 5-star hotels in Jinan, China. We sent out the surveys in three waves to avoid the common method bias. We obtained 199 valid responses in total in three waves and entered them into the data analysis. Structural equation modeling was conducted to examine our hypotheses. Results We found that network crafting was positively related to hotel employees’ work goal attainment and work-to-family facilitation. We also confirmed the mediating roles of positive affect and information exchange in this relationship. Conclusion We revealed a dual process of network crafting – that is, a positive affective process and an information exchange process. We contribute to the social network and networking literature by highlighting an optimization-oriented networking strategy, rather than one simply maximizing networks. We enrich the work-family enrichment literature by suggesting an effective behavioral strategy that can transmit the resources and gains from one domain to the other domain.